Efecto de la localización del partido en eliminatorias de ida y vuelta de la UEFA Champions League - Pic, M.; Castellano, J. (Revista Internacional de Ciencias del Deporte, 2016)
This research aims to investigate second leg home advantage in football. UEFA Champions League quarter-finals and semi-finals from 1954-55 season to 2013-14 season were analyzed, adding up to 642 matches and 336 playoffs. A non-parametric binomial contrast was applied to determine the influence of playing at home, while the binary logistic regression was used to show the explanatory proportion of goals after winning the qualifying round following the first confrontation. The main results showed that, in quarter-finals, local teams (second match) passed the qualifying round at higher rates than in semi-finals, in which visiting teams (second match) were classified at higher rates. From a strategic point of view, a better match-up game model and the selection of an alignment more consistent with the order of two-legged ties, will be some of the utilities offered by this work for coaches.